The effect of intramolecular donor–acceptor moieties with donor–π-bridge–acceptor structure on the solar photovoltaic performance - T. L. Wang; S. C. Huang; C. H. Yang; Y. Y. Chuang; C. H. Chen (eXPRESS Polymer Letters, 2015)
A series of intramolecular donor–acceptor polymers containing different contents of (E)-1-(2-ethylhexyl)-6,9-dioctyl-2-(2-(thiophen-3-yl)vinyl)-1H-phenanthro[9,10-d]imidazole (thiophene-DOPI) moiety and 4,4-diethylhexylcyclopenta[ 2,1-b:3,4-b']dithiophene (CPDT) unit was synthesized via Grignard metathesis (GRIM) polymerization. The synthesized random copolymers and homopolymer of thiophene-DOPI contain the donor–π-bridge–acceptor conjugated structure to tune the absorption spectra and energy levels of the resultant polymers. UV-vis spectra of the three polymer films exhibit panchromatic absorptions ranging from 300 to 1100 nm and low band gaps from 1.38 to 1.51 eV. It is found that more thiophene-DOPI moieties result in the decrease of band gap and lower the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) values of polymers. Photovoltaic performance results indicate that if the content of the intramolecular donor–acceptor moiety is high enough, the copolymer structure may be better than homopolymer due to more light-harvesting afforded by both monomer units.